Hydrogel Biomaterials for Application in Ocular Drug Delivery - Lynch, Courtney R.; Kondiah, Pierre P. D.; Choonara, Yahya E.; du Toit, Lisa C.; Ally, Naseer; Pillay, Viness (Frontiers in Bioengineering and Biotechnology, 2020)
There are many challenges involved in ocular drug delivery. These are a result of the many tissue barriers and defense mechanisms that are present with the eye; such as the cornea, conjunctiva, the blinking reflex and nasolacrimal drainage system. This leads to many of the conventional ophthalmic preparations having low bioavailability, rapid removal from the administration site and thus ineffective delivery of drugs. Hydrogels have been investigated as a delivery system which are able to overcome some of these challenges. These have been formulated as standalone systems or with the incorporation of other technologies such as nanoparticles. Hydrogels are able to be formulated in such a way that they are able to change from a liquid to gel as a response to a stimulus; known as "smart" or stimuli-responsive biotechnology platforms. Various different stimuli-responsive hydrogel systems are discussed in this article. Hydrogels are able to be formulated from both synthetic and natural polymers, known as biopolymers. This review focusses on the hydrogels which incorporate biopolymers. These are polymers have a number of benefits such as the fact that they are biodegradable, biocompatible and non-cytotoxic. The biocompatibility of the polymers used in ocular drug delivery systems because it is an extremely sensitive organ which is known as an immune-privileged site.